Controlled Incremental Filtration: A simplified approach to design and fabrication of high-throughput microfluidic devices for selective enrichment of particles - Gifford, Sean C. (Lab Chip, 2014)
The number of microfluidic strategies aimed at separating particles or cells of a specific size within a continuous flow system continues to grow. The wide array of biomedical and other applications that would benefit from successful development of such technology has motivated the extensive research in this area over the past 15 years. However, despite promising advancements in microfabrication capabilities, a versatile approach that is suitable for a large range of particle sizes and high levels of enrichment, with a volumetric throughput sufficient for large-scale applications, has yet to emerge. Here we describe a straightforward method that enables the rapid design of microfluidic devices that are capable of enriching/removing particles within a complex aqueous mixture, with an unprecedented range of potential cutoff diameter (below 1µm to above 100µm) and an easily scalable degree of enrichment/filtration (up to 10-fold and well beyond). A simplified model of a new approach to crossflow filtration – controlled incremental filtration – was developed and validated for its ability to generate microfluidic devices that efficiently separate particles on the order of 1–10µm, with throughputs of tens of µL/min, without the use of a pump. Precise control of the amount of fluid incrementally diverted at each filtration “gap” of the device allows for the gap size (~20µm) to be much larger than the particles of interest, while the simplicity of the model allows for many thousands of these filtration points to be readily incorporated into a desired device design. This new approach should enable truly high-throughput microfluidic particle-separation devices to be generated, even by users only minimally experienced in fluid mechanics and microfabrication techniques.